Variation of Permafrost Upper Limit in Permafrost Subgrade Covered by Snow on Steep Slope of Alpine Mountains - Zhilong Zhang; Xiancheng Li (Shock and Vibration)
The thermal insulation effect of snow on the active layer thickness of permafrost cannot be ignored. Under the dual influence of snow cover and roadbed construction, this paper studies the influence of snow cover on the temperature field and permafrost upper limit under the permafrost roadbed in the alpine mountains. Through the application of PDE module in Comsol software, the hydrothermal coupling analysis of roadbed is carried out by means of numerical analysis. The results show that the permafrost degradation is accelerated by the snow on the subgrade surface, the temperature increases significantly, the thickness of the active layer increases, and the permafrost upper limit moves downward. With the increase of seasonal snow thickness, the permafrost temperature under the subgrade increases, the low-temperature permafrost under the subgrade has the risk of changing to high-temperature permafrost. The melting groove is formed under the subgrade on the right side, and with the increase of snow thickness, the area of the melting groove expands and develops towards the center of the subgrade. Permafrost upper limit on the left and right shoulder is lower than that on the right shoulder, and snow cover has a greater impact on permafrost upper limit on the right shoulder.